Facial myokymia with hemifacial contracture as the sole manifestation of a pontine glioma: A clinical video - Kautilya R. Patel; Abhijit Goyal-Honavar; Dhaval Shukla; Ravi Yadav (Annals of Movement Disorders)
Facial myokymia is a rare clinical condition that manifests as subtle, involuntary and undulating “bag of worm-” like facial movements that is pathognomonic for brainstem pathology. Although most commonly the result of demyelinating disorders such as multiple sclerosis, it rarely portends a space-occupying lesion in the brainstem, with isolated case reports of brainstem gliomas, metastatic tumors, cysticercal cysts, or tuberculomas. Here, we present the case of a 22-year-old patient with left facial myokymia and left hemifacial contracture, which were the sole presenting signs of a brainstem glioma. This report demonstrates the characteristics of these innocuous clinical signs on a clinical video and emphasizes the need to suspect an infiltrative brainstem lesion in a patient with facial myokymia, indicating prompt evaluation with brain magnetic resonance imaging.